Kajian Adaptasi Beberapa Varietas Padi Pada Dua Tipologi Lahan di Sulawesi Tengah - Syafruddin Syafruddin; Andi Irmadamayanti; Saidah Saidah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Syafruddin et al, 2017. Study on Adaptation of Rice Varieties to Two Typical Lands in Central Sulawesi. JLSO 6(2):158-169. New paddy and rainfed rice fields have been potential resources in supporting sustainable rice self sufficiency. Improvemet on cultivation of adaptable varieties and good fertilization on the lands could increase production and land productivity.  This research aimed to findout new varieties adaptable to the typical lands with high yield.  The research was designed as randomized block design.  The treatments consisted of tree superior varieties and one ekxisting variety.  The results show that the areas are mainly less fertile with restriction factors: low in phosporus, low in organic content but high in iron.  The crop respons are mainly excellent to both types of the land in Poso and Donggala Regencies.  Banyuasin varietiety gave the highest production at both locations resulting in 9,13-9,27 tons/ha, followed by Mendawak and the existing varieties (Ciomas and Ciherang).  The results increased harvest up to 2,32-9,93 tons/ha compared to those cropped with Inpara 3.  The results also show that Banyuasin and the existing varieties are more adaptable and stable to both land types.  Based on suitability evaluation, the farms are grouped into suitable with B/C ratio 1,60-3,57 compared to Inpara 3 with B/C ratio 1,01- 1,59.